How do intraocular lens materials influence the outcome of cataract surgery? - Grzybowski, Andrzej; Auffarth, Gerd U.; LaHood, Benjamin R. (Current opinion in ophthalmology, 2025)
Purpose of review - This review summarizes the evidence on the effect of intraocular lens (IOL) material on the outcomes of cataract surgery, as well as on the surgical procedure itself. - Recent findings - Differences in capsular biocompatibility between IOL materials lead to variations in capsular stability and posterior capsule opacification (PCO), while differences in uveal biocompatibility affect postoperative inflammatory response. - Summary - Refractive outcomes are affected by both incision size and the rotational stability of toric IOLs. Small incision sizes favour hydrophilic IOLs. Rotational stability of hydrophobic and hydrophilic IOLs were comparable in recent studies. Visual outcomes are affected by chromatic aberrations, dysphotopsia, lens opacifications and PCO. Hydrophilic IOLs are associated with reduced chromatic dispersion. Hydrophobic IOL opacifications are caused by sub-surface glistenings, while hydrophilic IOL opacifications are due to surface calcifications. Some surgeries, including pars plana vitrectomy and lamellar corneal transplants, were shown to increase the risk of IOL calcifications, although the mechanism is still unknown. Hydrophilic IOLs have greater ease of manipulation, greater resistance to IOL damage, and higher uveal biocompatibility. Hydrophobic IOLs show better PCO prevention than hydrophilic IOLs, and should be preferred in highly myopic eyes where Nd:YAG capsulotomy might increase the risk of retinal detachment.